PENGARUH KINERJA LINGKUNGAN DAN PENGUNGKAPAN LINGKUNGAN TERHADAP MANAJEMEN LABA DENGAN KEPEMILIKAN KELUARGA SEBAGAI VARIABEL MODERASI - Zeta Zalmania Musyifaa, (2021)
This study aims to analyze the significant effect of environmental performance and environmental disclosure on earnings management with family ownership as a moderating variable in non-financial companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This study also uses control variables, namely firm size, leverage, profitability, and market to book ratio. Earnings management as the dependent variable is measured by the measurement of real earnings management (REM) by the model of Cohen et al. (2008). The independent variable of environmental performance is measured by the PROPER rating and environmental disclosure is measured by the GRI-G4 index and the GRI Standard. This study uses secondary data from annual reports, sustainability reports, and PROPER ranking lists with a total sample of 81. The results of this study prove that environmental performance and environmental disclosure have a positive and significant effect on earnings management. Then Family Ownership can moderate environmental performance on earnings management, but cannot moderate environmental disclosure on earnings management.